MOVES – I. The evolving magnetic field of the planet-hosting star HD189733. Issue 1 (26th June 2017) - Fares, R.; Bourrier, V.; Vidotto, A. A.; Moutou, C.; Jardine, M. M.; Zarka, P.; Helling, Ch.; Lecavelier des Etangs, A.; Llama, J.; Louden, T.; Wheatley, P. J.; Ehrenreich, D.
Abstract: HD189733 is an active K dwarf that is, with its transiting hot Jupiter, among the most studied exoplanetary systems. In this first paper of the Multiwavelength Observations of an eVaporating Exoplanet and its Star (MOVES) programme, we present a 2-yr monitoring of the large-scale magnetic field of HD189733. The magnetic maps are reconstructed for five epochs of observations, namely 2013 June–July, 2013 August, 2013 September, 2014 September and 2015 July, using Zeeman–Doppler imaging. We show that the field evolves along the five epochs, with mean values of the total magnetic field of 36, 41, 42, 32 and 37 G, respectively. All epochs show a toroidally dominated field. Using previously published data of Moutou et al. and Fares et al., we are able to study the evolution of the magnetic field over 9 yr, one of the longest monitoring campaigns for a given star. While the field evolved during the observed epochs, no polarity switch of the poles was observed. We calculate the stellar magnetic field value at the position of the planet using the potential field source surface extrapolation technique. We show that the planetary magnetic environment is not homogeneous over the orbit, and that it varies between observing epochs, due to the evolution of the stellar magnetic field. This result underlines the importance of contemporaneous multiwavelength observations to characterize exoplanetary systems. Our reconstructed maps are a crucial input for the interpretation and modelling of our MOVES multiwavelength observations.